FEATURES OF AN ECONOMIC APPROACH AT RESEARCH OF CORRUPTION PHENOMENON - M.O. Izotov (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
In article features of an economic approach are considered when developing the anti-corruption measures directed on restriction of possibilities of any discretion and excessive intervention of civil servants in economic activity, including through differentiation of functions and specification of competences. The special urgency of researches of a problem of corruption as special social phenomenon is noted.